Persepsi dan Representasi Perempuan Dalam Budaya Arab: Tinjauan Pustaka - Abdullah Sami (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines the perception and representation of women in Arab culture through a systematic literature review. Using postcolonial feminist theory, intersectionality, and media representation theory, this research analyzes how Arab women are portrayed in global and local media, as well as the historical evolution of their roles in society. Through qualitative analysis of academic literature, media content, and cultural documents from 1990-2023, the study reveals complex dynamics in how Arab women are perceived and represented. The findings highlight significant gaps between media representation and reality, the impact of modernization on gender roles, and the emergence of new paradigms in understanding Arab women's identities. The research contributes to a more nuanced understanding of Arab women's experiences while highlighting the importance of contextual and intersectional approaches in gender studies. The implications of this study suggest the need for more balanced representation and policy development that supports Arab women's empowerment while respecting cultural values.